2008
DOI: 10.1016/j.jvs.2007.10.060
|View full text |Cite
|
Sign up to set email alerts
|

High ligation combined with stripping and endovenous laser ablation of the great saphenous vein: Early results of a randomized controlled study

Abstract: Endovenous laser ablation combined with high ligation is safe and effective. Postoperative hematomas are significantly smaller than those after stripping. Short-term quality of life is at least as good as that after stripping. The long-term results warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 25 publications
1
63
1
8
Order By: Relevance
“…Concerning the patients' overall satisfaction with the treatment, the available studies do not present any statistically significant results [25,30,34,35]. Although in our study a slightly higher percentage of patients who received open surgery claimed that they would choose the same technique again or would recommend it to their relatives or friends, the difference between the surgery and the EVLA groups was not statistically significant.…”
Section: Discussioncontrasting
confidence: 71%
“…Concerning the patients' overall satisfaction with the treatment, the available studies do not present any statistically significant results [25,30,34,35]. Although in our study a slightly higher percentage of patients who received open surgery claimed that they would choose the same technique again or would recommend it to their relatives or friends, the difference between the surgery and the EVLA groups was not statistically significant.…”
Section: Discussioncontrasting
confidence: 71%
“…Surgical or endovenous ablation of saphenous veins improves quality of life in the long term and helps symptoms subside. Comparison of saphenous vein ablation and surgery regarding change in quality of life showed similar results in the long term (1)(2)(3)(4)(5)(6). However, in the early postoperative period, patients who had laser ablation experienced a greater improvement in quality of life, a faster return to work and a quicker return to normal activities (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 84%
“…In the literature, the greatest clinical benefit was reportedly obtained in the first three to six months after treatment, with no further clinical improvement possible after six months (3)(4)(5)(6)(7). Therefore, the best time to evaluate the response to treatment appeared to be at month six.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, these studies document, at least initially, an effective elimination of the epifascial reflux through ELT accompanied by reduced side effects. Whether refraining from cross- [24] GB 103 ELT vs. crossectomy/stripping Kalteis et al [25] A 95 ELT vs. crossectomy/stripping Disselhoff et al [26,27] NL 120 ELT vs. crossectomy/cryostripping ectomy in fact leads to increased incidence of inguinal neo-reflux or even to a reduction of neo-vascularization at the sapheno-femoral junction will have to be shown in further controlled trials and, in particular, in further post-operative examinations of already randomized patients.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…As shown in figure 2 the divergence angle of the emitting beam (full width at half maximum) could be determined to be [25][26][27][28][29][30] . The fiber robustness experiments showed that the fiber keeps intact without any damage when a power of 10 W for 30 s had been applied.…”
Section: Resultsmentioning
confidence: 99%